A general equilibrium approach of retail payments - Tamás Ilyés; Lóránt Varga (Magyar Nemzeti Bank, 2015)
In our paper, we introduce the Hungarian Payment System Model (HUPS), a computable general equilibrium model with detailed payment services which can be used for policy evaluation and forecast. In the last years, several studies investigated different aspects of payment systems and some papers used equilibrium theory to study a specific segment or question of retail payments. In our paper, we take a step forward as we extend this research using the general equilibrium approach. The HUPS model is a large and highly disaggregated computable general equilibrium model with 25 economic agents and nearly 100 payment services, which cover most of the payment system supply chain in Hungary. It contains 7 types of costs for each payment service, varying degree of economies of scale, oligopoly and cross-product pricing and agent behaviour adjustments to payment method costs. In our model, the payment sector is an integrated part of the economy as every actor has to make payment decisions related to its activities. As a result, the model can be used for thorough economic evaluation of many kinds of policies and other changes in the field of retail payments. The HUPS model is calibrated on the large and up-to-date information base of Hungarian payment statistics, surveys and studies - most notably the Hungarian cost of payments study - which makes it a powerful and robust modelling and forecasting tool.
Keywords: C68; E27; E42; 330; payment economics; CGE modelling; retail payments; cost of payments